Meningkatkan Kompetensi Evaluasi Pembelajaran melalui Pelatihan Analisis Butir Soal bagi Mahasiswa Calon Guru - Muh. Bahly Basri; Sultan Sultan; Muhammad Rapi; Baharman Baharman; Sakaria Sakaria (MALLOMO: Journal of Community Service, 2025)
The ability to conduct item analysis is one of the essential competencies that prospective teachers must have in the context of learning evaluation. However, in reality, many prospective teachers do not have adequate understanding and skills in analyzing the quality of questions quantitatively, especially in measuring the level of difficulty and the index of distinguishing power. This community service activity aims to improve the competence of prospective student teachers through practice-based item analysis training. The method used in this activity is structured training which includes providing conceptual material, practicing manual and digital calculations using Microsoft Excel, discussions, and pretest and posttest evaluations. The results of the training showed a significant increase in participants' understanding of the concept of item analysis and their ability to apply it technically. In addition, participants showed high enthusiasm and stated that the training was very relevant to their needs as future educators. This activity makes an important contribution in preparing students to face professional challenges as teachers who are able to design and evaluate assessments objectively and with quality.